A novel ENPP1 mutation identified in a multigenerational family affected by Cole disease. Issue 5 (29th June 2020) - Gabaton, Niña; Kannu, Peter; Pope, Elena; Shugar, Andrea; Lara‐Corrales, Irene
Abstract: Cole disease is a rare autosomal dominant genodermatosis with only five cases published in literature since its first description in 1976. We report a case of a 3‐year‐old boy of Italian ancestry who presented with hypopigmented skin patches on the upper extremities and multiple yellowish, firm papules and small plaques on his palms and soles. There were similar findings in the family, extending back at least four generations. Whole exome sequence analysis revealed a novel variant of the ENPP1 gene mutation, which has not been previously reported to be associated with Cole disease. Although there is no extracutaneous involvement associated with this condition, accurate diagnosis and variant identification is nevertheless important so that appropriate medical and genetic counseling can be offered to affected individuals and their at‐risk relatives.